Rationale and design of the registry of acute stroke under novel oral anticoagulants-prime (RASUNOA-prime): $hKirsten Haas, Jan C. Purrucker, Timolaos Rizos, Peter U. Heuschmann and Roland Veltkamp - Haas, Kirsten; Purrucker, Jan; Rizos, Timolaos; Heuschmann, Peter U.; Veltkamp, Roland (European stroke journal, 2019)
BackgroundAnticoagulation with vitamin K antagonists and non-vitamin K antagonists oral anticoagulants (NOAC) is effective in stroke prevention in patients with atrial fibrillation. However, antico...
Published online: 17 December 2018
Gesehen am 01.04.2020